Screening mammography with special reference to guidelines in South Africa - Shirley Lipschitz (South African Journal of Radiology, 2018)
Screening mammography is known to reduce mortality from breast cancer. Controversy regarding screening has led to much confusion in the medical fraternity. The purpose of this review is to point out the ‘pros and cons’ of screening. The benefits and perceived harms of screening will be discussed using evidence-based literature from the past 30 years. The literature was obtained from various journals sourced from the Internet. General findings are that screening mammography from the age of 40 saves lives, but that the problem of overdiagnosis and overtreatment of certain breast cancers overrides the benefit of screening. The article also covers the debate on what age to begin screening. Screening in the South African context is discussed. Screening in the future will need to be more selective of patients and of which cancers to treat less aggressively, if at all.